CAPILLARY ELECTROPHORETIC ANALYSIS OF LOW-MOLECULAR-MASS OF CA SPECIES IN PHLOEM SAP OF Ricinus communis L. - Noor Fitri; Björn Thiele; Klaus Günther; Buchari Buchari (Universitas Gadjah Mada, 2006)
A capillary electrophoretic (CE) analysis with ultra-violet (UV) detection was performed for further separation of low-molecular-mass (LMM) calcium species in phloem sap of Ricinus communis L. Two different background electrolytes (BGE) were used for the separation; these are (1) hydrogen phosphate/dihydrogen phosphate buffer containing cetyltrimethylammonium bromide (CTAB) as an electro-osmotic flow (EOF) modifier, and (2) boric acid buffer containing CTAB. Various parameters affecting the analysis, including the composition and pH of the BGE were systematically studied. The sensitivity, resolution, baseline noise, migration time of the species peaks, and reproducibility of the method were evaluated under optimised condition. At least 13 UV-active species were optimally separated within about ten minutes. The optimised measurement condition was also achieved using 10 mM hydrogen phosphate/10 mM dihydrogen phosphate containing 0.5 mM CTAB at pH 8.0 as BGE, and by applying voltage of ‑20 kV and temperature of 14°C. Evidently, the analytical method was successfully used for the separation of LMM calcium species in phloem sap of R. communis L.